Oxidative Stress and Inflammation: Essential Partners in Alcoholic Liver Disease. (1st March 2012) - Ambade, Aditya; Mandrekar, Pranoti
Abstract : Alcoholic liver disease (ALD) is a multifaceted disease that is characterized by hepatic steatosis or fat deposition and hepatitis or inflammation. Over the past decade, multiple lines of evidence have emerged on the mechanisms associated with ALD. The key mechanisms identified so far are sensitization to gut-derived endotoxin/lipopolysaccharide resulting in proinflammatory cytokine production and cellular stress due to oxidative processes, contributing to the development and progression of disease. While oxidative stress and inflammatory responses are studied independently in ALD, mechanisms linking these two processes play a major role in pathogenesis of disease. Here we review major players of oxidative stress and inflammation and highlight signaling intermediates regulated by oxidative stress that provokes proinflammatory responses in alcoholic liver disease.